Type I Interferons Are Involved in the Intracellular Growth Control of Mycobacterium abscessus by Mediating NOD2-Induced Production of Nitric Oxide in Macrophages - Ahn, Jae-Hun; Park, Ji-Yeon; Kim, Dong-Yeon; Lee, Tae-Sung; Jung, Do-Hyeon; Kim, Yeong-Jun; Lee, Yeon-Ji; Lee, Yun-Ji; Seo, In-Su; Song, Eun-Jung; Jang, Ah-Ra; Yang, Soo-Jin; et al. (Frontiers in Immunology, 2021)
Mycobacterium abscessus (MAB) is one of rapid growing, multidrug resistant nontuberculous mycobacteria (NTM) causing various diseases including pulmonary disorder. Although it has been known that Type I interferons (IFNs) contribute to host defense against bacterial infections, the role of type I IFNs against MAB infection is still unclear. In the present study, we show that rIFN-β treatment reduced the intracellular growth of MAB in macrophages. Deficiency of IFNAR led to the reduction of nitric oxide (NO) production in MAB-infected macrophages. Consistently, rIFN-β treatment enhanced the expression of iNOS gene and protein and NO production in response to MAB. We also found that NO is essential for the intracellular growth control of MAB within macrophages in an inhibitor assay using iNOS-deficient cells. In addition, pretreatment of rIFN-β before MAB infection in mice increased production of NO in the lungs at day 1 after infection and promoted the bacterial clearance at day 5. However, when alveolar macrophages were depleted by treatment of clodronate liposome, rIFN-β did not promote the bacterial clearance in the lungs. Moreover, we found that a cytosolic receptor nucleotide-binding oligomerization domain 2 (NOD2) is required for MAB-induced TBK1 phosphorylation and IFN-β gene expression in macrophages. Finally, increase in the bacterial loads caused by reduction of NO levels was reversed by rIFN-β treatment in the lungs of NOD2-deficient mice. Collectively, our findings suggest that type I IFNs act as an intermediator of NOD2-induced NO production in macrophages and thus contribute to host defense against MAB infection.